In silico approach to identify microsatellite candidate biomarkers to differentiate the biovar of Corynebacterium pseudotuberculosis genomes - Pinheiro, Kenny da Costa; Gois, Bruna Verônica Azevedo; Nogueira, Wylerson Guimarães; Araújo, Fabrício Almeida; Queiroz, Ana Lídia Cavalcante; Cardenas-Alegria, Oscar; da Silva, Artur Luiz da Costa; Júnior, Antônio Márcio Gomes Martins; Ramos, Rommel Thiago Jucá (Frontiers in Bioinformatics, 2022)
Corynebacterium pseudotuberculosis is the causative bacterial agent of the zoonotic disease known as Caseous Lymphadenitis, and it presents several mechanisms of response to host defenses, including the presence of virulence factors (VFs). The genomes of these bacteria have several polymorphic markers known as microsatellites, or Simple Sequence Repeats (SSRs), that can be used to characterize the genome, to study possible polymorphisms existing among strains, and as well as to verify the effects of such polymorphic markers in coding regions and regions associated with VFs. In this study, several SSRs were identified within coding regions throughout the 54 genomes of this species, revealing possible polymorphisms associated with coding regions that could be used as strain-specific or serotype-specific identifiers of C. pseudotuberculosis. The similarities associated with SSRs amongst the different serum variants of C. pseudotuberculosis, biovars equi and ovis, were also evaluated, and it was possible to identify SSRs located in coding regions responsible for a VF enrolled in pathogenesis known to mediate bacterial adherence (SpaH-type pili virulence factor). Phylogenetic analyses revealed that strains sharing SSR patterns, including the possible polymorphisms identified in the same position of gene coding regions, were displayed by strains with a common ancestor, corroborating with the Genome Tree Report of the NCBI. Statistical analysis showed that the microsatellite groups belonging to biovars equi and ovis have a significance of 0.006 (p_value) in similarity, thus indicating them as good biomarker candidates for C. pseudotuberculosis.